Kejahatan Lingkungan di Indonesia Era Modern: Tantangan, Aktor, dan Kesenjangan Penegakan Hukum - Rynaldi, Alfredo (Sisi Lain Realita Another Side Of Reality Journal Criminology, 2026)
Environmental crime represents one of the most pressing threats to global ecological sustainability in the modern era. This study aims to examine the multidimensional nature of environmental crime by analyzing its typologies, key actors, enforcement challenges, and regulatory gaps. Employing a qualitative approach based on literature review and document analysis, the study draws on insights from Green Criminology to understand environmental harm beyond formal legal definitions. The findings reveal that environmental crime is increasingly transnational in nature, involving organized criminal networks and complex interactions between state and corporate actors. In many developing countries, weak governance structures and regulatory failures create enabling conditions that facilitate such crimes. These dynamics reflect patterns consistent with state-corporate crime, where state policies and institutional limitations indirectly support environmentally harmful practices. Furthermore, the study identifies a significant gap between existing legal frameworks and actual enforcement capacity, resulting in low prosecution rates and limited deterrence. This enforcement gap underscores the need to move beyond formal compliance and address structural conditions that perpetuate environmental harm. This study recommends strengthening international cooperation, enhancing institutional capacity for environmental law enforcement, and integrating green criminological perspectives into criminal justice systems. Such measures are essential to address the evolving and complex challenges of environmental crime in the contemporary era.